Physical Characteristic and Antibacterial Activity of Silver Nanoparticles from Green Synthesis Using Ethanol Extracts of Phaleria macrocarpa (Scheff.) Boerl Leaves - Tri Puji Lestari; Fitia Abbas Tahlib; Johan Sukweenadhi; Kartini kartini; Christina Avanti (Faculty of Pharmacy, Universitas Gadjah Mada, 2019)
The Green Synthesis method is widely developed due to its environmentally friendly, cost-effective, and easy application for nanoparticle-scale synthesis. Among all metal nanoparticles, silver nanoparticles are the most utilized products in the field of nanotechnology. Biomolecules contained in plant extracts can reduce the size of silver particles to nano size. This study aims to determine the antibacterial properties and activity of silver nanoparticles synthesized with the ethanol extract of mahkota dewa leaves. The formation of silver nanoparticles is monitored with UV-Vis absorption and its change in color. Parameters evaluated are shape, size, particle size distribution, composition, metal residue, and a functional group of nanoparticles, using Scanning Electron Microscopy (SEM), Particle Size Analyzer (PSA), X-Ray Diffraction (XRD), and Fourier Transform InfraRed (FTIR) instrument. The research on UV-Vis color and absorption show black silver color with the wavelength of 450-465nm. The characterization result shows spherical-shaped silver nanoparticle. Furthermore, PDI best value on concentration of 0.125% is 0,221±0,0482 with average particle size of 130,300±12,6858 nm. The diffraction pattern of silver nanoparticle with XRD test indicates that the nanoparticles contain the silver component. Antibacterial activity test shows that silver nanoparticles have a greater inhibition zone than AgNO3, and 0.125% ethanol extract of mahkota dewa leaves against Escherichia coli and Staphylococcus aureus. From the results of the study, it can be concluded that the ethanol extract from mahkota dewa leaves can be used as a bioreductor agent to produce silver nanoparticles which have greater antimicrobial activity compared to Ag and ethanol extract from mahkota dewa leaves.